Genome editing in rice mediated by miniature size Cas nuclease SpCas12f - Sukegawa, Satoru; Nureki, Osamu; Toki, Seiichi; Saika, Hiroaki (Frontiers in Genome Editing, 2023)
Cas9 derived from Streptococcus pyogenes (SpCas9) is used widely in genome editing using the CRISPR-Cas system due to its high activity, but is a relatively large molecule (1368 amino acid (a.a.) residues). Recently, targeted mutagenesis in human cells and maize using Cas12f derived from Syntrophomonas palmitatica (SpCas12f)—a very small Cas of 497 a.a., which is a more suitable size for virus vectors—was reported. However, there are no reports of genome editing using SpCas12f in crops other than maize. In this study, we applied SpCas12f to genome editing in rice—one of the most important staple crops in the world. An expression vector encoding rice codon-optimized SpCas12f and sgRNA for OsTubulin as a target was introduced into rice calli by Agrobacterium-mediated transformation. Molecular analysis of SpCas12f-transformed calli showed that mutations were introduced successfully into the target region. Detailed analysis by amplicon sequencing revealed estimated mutation frequencies (a ratio of the number of mutated calli to that of SpCas12f-transformed calli) of 28.8 and 55.6% in two targets. Most mutation patterns were deletions, but base substitutions and insertions were also confirmed at low frequency. Moreover, off-target mutations by SpCas12f were not found. Furthermore, mutant plants were regenerated successfully from the mutated calli. It was confirmed that the mutations in the regenerated plants were inherited to the next generation. In the previous report in maize, mutations were introduced by treatment with heat shock at 45 oC for 4 hours per day for 3 days; no mutations were introduced under normal growth conditions at 28 oC. Surprisingly, however, mutations can be introduced without heat-shock treatment in rice. This might be due to the culture conditions, with relatively higher temperature (30 oC or higher) and constant light during callus proliferation. Taken together, we demonstrated that SpCas12f can be used to achieve targeted mutagenesis in rice. SpCas12f is thus a useful tool for genome editing in rice and is suitable for virus vector-mediated genome editing due to its very small size.